2019
DOI: 10.1111/jrh.12358
|View full text |Cite
|
Sign up to set email alerts
|

Rural and Urban Differences in the Adoption of New Health Information and Medical Technologies

Abstract: Background: This statewide survey sought to understand the adoption level of new health information and medical technologies, and whether these patterns differed between urban and rural populations.Methods: A random sample of 7,979 people aged 18-75 years, stratified by rural status and race, who lived in 1 of 34 Indiana counties with high cancer mortality rates and were seen at least once in the past year in a statewide health system were surveyed.Results: Completed surveys were returned by 970 participants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 32 publications
4
19
0
Order By: Relevance
“…The demographic profiles and generalizability of our study sample have been reported elsewhere. 9,10 In short, our study sample is largely consistent with estimates of the population. However, we mailed enough surveys to obtain a relatively large absolute number of surveys among rural and African-American individuals, two groups among whom we were concerned about the presence of disparities in access to health information technologies.…”
Section: Resultssupporting
confidence: 73%
“…The demographic profiles and generalizability of our study sample have been reported elsewhere. 9,10 In short, our study sample is largely consistent with estimates of the population. However, we mailed enough surveys to obtain a relatively large absolute number of surveys among rural and African-American individuals, two groups among whom we were concerned about the presence of disparities in access to health information technologies.…”
Section: Resultssupporting
confidence: 73%
“…The survey methodology has been described in more detail elsewhere. [11] Populations eligible for cancer screening…”
Section: Study Cohortmentioning
confidence: 99%
“…This cross-institutional collaboration allowed awardees to reach a consensus on measures of rurality and other integral variables to bolster the reach and integrity of their research efforts. A special section of The Journal of Rural Health was published in 2019 to highlight work of the rural working group (8)(9)(10)(11)(12). The catchment area P30 supplement initiative was reissued in fiscal year 2018, and 14 additional cancer centers were awarded, with seven of the 14 centers participating in the rural working group.…”
Section: Building Rural Cancer Control Research Capacitymentioning
confidence: 99%